Does jumping conducted before the swimming start elicit underwater enhancement? - Ruiz-Navarro, J. J.; Cuenca-Fernández, F.; Papic, C.; Gay, A.; Morales-Ortíz, E.; López-Contreras, G.; Arellano, R. (International Journal of Sports Science & Coaching, 2023)
The effects of pre-activation exercises on undulatory underwater swimming (UUS) have not been studied. This research aimed to: 1) assess the effects of a jumping-exercise strategy upon UUS performance and kinematics variables; 2) test the different effects on males and females, and; 3) to explore if stronger participants exhibit greater post-activation performance enhancement (PAPE). Ninety-two age-group national level swimmers randomly assigned into control (17 males and 18 females) and experimental groups (27 males and 30 females) took part in a cross-sectional study designed to test two maximal 15-m UUS performance efforts. The experimental group performed four maximal tuck jumps before the first or the second UUS effort. Performance and kinematics variables were analyzed using instantaneous velocity data via speedometer. Maximal lower-limbs force was obtained during a countermovement jump through a linear-encoder. Two-way repeated measures ANOVA test and linear regression analysis were used to explore variable interactions between baseline and PAPE, and the association between the PAPE response and strength of the swimmers, respectively. Despite trends toward improvements in push-off velocity (? = 1.33%; d = 0.12), the results did not show enhancements nor deterioration in UUS performance and kinematics after the tuck jumps. No specific PAPE responses modulated by sex or by the strength level of the swimmers were observed for this age-group (p < 0.05). Four tuck jump repetitions executed prior to diving could be insufficient to acutely enhance UUS performance. The fact that the exercise performed during warm-up was a body-weight based exercise, was possibly not enough to evoke PAPE.